P231 The use of indwelling pleural catheters in patients with malignant pleural effusion and unexpandable lung. (15th November 2017) - Halford, P; Bhatnagar, R; Maskell, NA
Abstract : Introduction: British Thoracic Society (BTS) guidelines suggest that Indwelling Pleural Catheters (IPCs) are the best treatment for malignant pleural effusion (MPE) associated with unexpandable lung (UL), where pleurodesis is contraindicated. Although, comprehensive data highlight the benefit of IPCs in MPE, their efficacy in patients with UL is less well known. Method: We conducted a systematic review following searches of the MEDLINE, EMBASE and Web of Science databases up until June 2017. Studies specifically reporting IPC use in patients with MPE and UL were identified. Results: 24 studies using IPCs in MPE in general were analysed, 15 of which stated the proportion with UL. Only 3 trials specifically reported outcomes in patients with UL, ranging from 11–52 patients. 77%–94% of UL patients had symptomatic benefit with IPC. Complication rate ranged from 15%–56% depending on criteria used, common complications reported included pain, cellulitis, catheter leak and occlusion. Self-pleurodesis in the largest trial occurred in 42.3% Mean hospital stay was three days, however only one study reported this. Mortality was mentioned in two papers, with a mean survival of 126 days post-IPC insertion. Incidence of UL in the MPE population undergoing IPC was calculable in five studies, and ranged from 7.5%–41%. Differences were evident depending on criteria for diagnosing UL. One study using video-assisted thoracoscopy in 127 patients had an incidence of 41% whereas another study using post-procedure radiography found UL in 40/295 IPCs (13.6%). Conclusion: There appears to be symptomatic benefit in using IPCs in UL patients. Although complications tended to be relatively minor, their rates appear increased compared to the broader IPC population. However, the lack of consensus in diagnostic criteria for UL, reflected by the varied incidence reported, makes application harder to interpret. Further evidence is needed to establish a consistent approach to UL diagnosis, along with more robust studies addressing incidence. The use of IPCs in this population also needs further, prospective, study, with a focus on patient-centred outcomes and device efficacy. This would ideally include further validation of the finding that IPC's in UL can lead to pleurodesis in a large number of patients.